Power converters used in wind turbine system - Muhammad Zainudin Sainal. (2011)
With the rapid increase in demand for renewable energy to provide solutions for environmental concerns and decreasing natural resources, renewable energy have been used to meet this demand, such as wind energy. Hence, there is a need to utilise power electronics technique for effective power conversion. As the voltage and current from renewable energy sources are unstable, many efficient circuits solving this problem are created. Wind turbine system uses DC/AC, DC/DC and DC/AC to convert the unstable voltage and frequency to a stable voltage to be connected to the power grid. In this report, simulation of wind turbines power converters and superlift luo converter hardware design are conducted. Simulation is done with the aid of PSIM software. It was found that the superlift luo converter was feasible to be incorporated into the wind turbine power converters design as the output voltage met the design specifications.